Making public media personal: Nostalgia and reminiscence in the office - Sellen, Abigail; Schraefel, mc; Wood, Ken (Proceedings of the 25th BCS Conference on HCI (British HCI 2011), 2011)
In this paper we explore the notion of creating personally evocative collections of content from publicly available material. Compared to the personal media that we look at, reminisce over, or personalise our offices with, public media offers the potential for a different type of nostalgia, signifiers of an era such as entertainment, products, or fashions. We focus on an office environment, where the use of filtered public media may mitigate concerns over protecting privacy and disclosing too much of one's identity, while keeping the existing benefits of office personalisation in terms of reminiscence, improving mood, and developing identity. After preliminary explorations of content and form, we developed a two-screen ambient display that cycled through 500 images automatically retrieved based on four simple user questions. We ran a two-week trial of the display with six users. We present qualitative results of the trial from which we see that it is possible to bring the delight associated with personal content into the workplace, while being mindful of issues of appropriateness and privacy. Images of locations from childhood were particularly evocative for all participants, while simple objects such as stickers, music, or boardgames were more varied across participants. We discuss a number of avenues for future work in the workplace and beyond: improving the chance of an evocative moment, capturing the mundane, and the crowdsourcing of nostalgia.